Jeff Koons – a spectacle on the way to respectable - Messham-Muir, Kit (The Conversation Media Group, 2014)
American Jeff Koons is possibly the most contentious living artist. His current retrospective at the Whitney Museum in New York writes him into the contemporary canon of great living artists – but even after a long and controversial career, that hasn’t been an easy case to make.